Effectiveness of intensive treatment services for obsessive compulsive disorder: outcomes from the first Canadian residential treatment program. (2nd January 2020) - Taube-Schiff, Marlene; Rector, Neil A.; Larkin, Persephone; Mehak, Adrienne; Richter, Margaret A.
Abstract: Background: Obsessive–Compulsive Disorder (OCD) is a psychiatric illness that can result in debilitating symptoms and functional impairment. Until recently, individuals with severe OCD symptoms have not received appropriate services within the Canadian healthcare system. The Frederick W. Thompson Anxiety Disorders Centre launched an Intensive Services Residential treatment programme for OCD in July 2017 to meet the needs of the Canadian population. This paper sets out to demonstrate the effectiveness of this programme. Methods: This study incorporated quantitative and qualitative data collection. Quantitative data were analysed using paired sample t -tests while qualitative data was transcribed and coded for emerging themes. Results: Beneficial changes in symptomatology were found. Client narrative emphasised the importance of exposure response prevention (ERP), creation of an OCD community as well as enhanced functionality in clients' lives. Clients also commented on why they believed the treatment worked and points of potential improvement for discharge planning and programme organisation. Conclusions: This study adds to the growing body of evidence regarding the importance of intensive services for individuals experiencing severe symptoms of OCD. Enhancing accessibility to services and ensuring ongoing maintenance of gains will be important next steps in ensuring long-term recovery for individuals with severe symptoms of OCD. Key points: Intensive services treatment for OCD has been found to be beneficial for clients and this paper demonstrates the first time this has been seen within a Canadian programme. Treatment provided decreased OCD severity and increased functionality and quality of life. Clients cited exposure and response prevention work as a key ingredient in their recovery. Our programme is always in an ongoing state of quality improvement, ensuring client engagement and satisfaction.